How Therapists Change: Personal and Professional Reflections. 2001
DOI: 10.1037/10392-008
|View full text |Cite
|
Sign up to set email alerts
|

Making meaning of therapy: A personal narrative of change over 4 decades.

Abstract: He who lives his life in genuine realizing knowledge, must perpetually begin anew, perpetually risk all anew; and thus his truth is not a having, but a becoming. (Martin Buber, 1913/1964 90) I consider myself an integrative therapist. This chapter describes my training and experiences in four different therapy modalities spanning the 4 decades that have formed the foundation of my work. My original training as a graduate student in the late 1950s to mid-1960s featured a Freudian psychoanalytic orientation. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Even though he tried to learn behavioral therapy as precisely as possible, he found himself assimilating it into his psychoanalytic understanding rather that adopting it as such. We found similar indications in Fodor's (2005) narrative: first, she adhered to psychoanalysis, later describing a more intrinsic adherence toward cognitive-behavioral therapy which ultimately became the basis of her personal approach (later combined with Gestalt therapy). Castonguay's (2006) narrative also suggested that in his case the cycle repeated twice: first, being exposed to multiple orientations at the beginning of his career, he faced a state of confusion.…”
Section: Phase Repetitionsupporting
confidence: 62%
See 1 more Smart Citation
“…Even though he tried to learn behavioral therapy as precisely as possible, he found himself assimilating it into his psychoanalytic understanding rather that adopting it as such. We found similar indications in Fodor's (2005) narrative: first, she adhered to psychoanalysis, later describing a more intrinsic adherence toward cognitive-behavioral therapy which ultimately became the basis of her personal approach (later combined with Gestalt therapy). Castonguay's (2006) narrative also suggested that in his case the cycle repeated twice: first, being exposed to multiple orientations at the beginning of his career, he faced a state of confusion.…”
Section: Phase Repetitionsupporting
confidence: 62%
“…Integration as an explicit goal (n ‫؍‬ 10, 45%) versus integration as a natural "side-effect" of development (n ‫؍‬ 12, 55%). The development of a new, integrative psychotherapeutic approach was an explicit goal for only some of the psychotherapists (Castonguay, 2006;Fodor, 2005;Giovazolias, 2005;Greenberg, 2005;Lampropoulos, 2006a;Norcross, 2006;Nuttall, 2008;Wachtel, 2005;Watson, 2006;Wolfe, 2005). Furthermore, some of these same psychotherapists demonstrated integrative tendencies even at the very beginning of their careers, creating their own conceptual frameworks (e.g., Bohart, 2005;Giovazolias, 2005;Wolfe, 2005).…”
Section: Consolidation Phase (N ‫؍‬ 21 95%)mentioning
confidence: 99%
“…From my earliest work as a Freudian therapist, where I was the “special friend” for lonely children in pain, to my current work with adults, who come to me seeking some refuge from the loneliness, insensitivity, and abuse they experience in the outside world, I see the therapeutic encounter as an opportunity for clients to explore their experiences, learn about themselves, and learn how to cope in a safe place with someone who tries to understand them, who meets them as another human being, and who has struggled to cope and make sense of life. (Fodor, , p. 124)…”
Section: My Journey: Introductionmentioning
confidence: 99%